2006
DOI: 10.1016/j.trstmh.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of familial neurocysticercosis in an endemic Mexican community

Abstract: Neurocysticercosis (NC) caused by Taenia solium is a frequent parasitic disease of the central nervous system. It is highly endemic in many developing countries, where many people are exposed but few become infected. Here, the relevance of age, gender, and genetic and exposure factors on NC susceptibility was studied in 649 inhabitants of a rural community of Mexico. Endemicity was confirmed by the high prevalence of pig cysticercosis (32.8%) and human seroprevalence (43.8%). Human NC cases were diagnosed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 44 publications
2
39
0
3
Order By: Relevance
“…This disease represents a major public health problem in areas of endemicity in Latin America, Africa, and Asia (18,29,33,36) and has been diagnosed with increasing frequency in the United States, primarily as an imported disease (8). In Mexico, seroprevalence rates for human cysticercosis ranged from 3.7 to 12.2% (18), and computerized-tomography (CT)-based epidemiological studies performed on inhabitants of rural communities have found an NC prevalence as high as 10% (14,17).…”
mentioning
confidence: 99%
“…This disease represents a major public health problem in areas of endemicity in Latin America, Africa, and Asia (18,29,33,36) and has been diagnosed with increasing frequency in the United States, primarily as an imported disease (8). In Mexico, seroprevalence rates for human cysticercosis ranged from 3.7 to 12.2% (18), and computerized-tomography (CT)-based epidemiological studies performed on inhabitants of rural communities have found an NC prevalence as high as 10% (14,17).…”
mentioning
confidence: 99%
“…Estos resultados concuerdan con la mayoría de los estudios epidemiológicos de Venezuela (26,28,30) y de otros países latinoamericanos (13,16,20).…”
Section: Discussionunclassified
“…In humans and pigs, the parasite is frequently located in the central nervous system (CNS), causing neurocysticercosis (NC) (De Aluja & Vargas 1988;Fleury et al 2006a;Prasad et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Human NC may be asymptomatic (Briceñ o et al 1961;Villagran & Olvera 1988;Fleury et al 2003Fleury et al , 2006a but it can also be manifested by a wide variety of unspecific signs and symptoms (i.e. seizures, headache, etc.)…”
Section: Introductionmentioning
confidence: 99%